Two Novel Ceramide-Like Molecules and miR-5100 Levels as Biomarkers Improve Prediction of Prostate Cancer in Gray-Zone PSA - Mello-Grand, Maurizia; Bruno, Antonino; Sacchetto, Lidia; Cristoni, Simone; Gregnanin, Ilaria; Dematteis, Alessandro; Zitella, Andrea; Gontero, Paolo; Peraldo-Neia, Caterina; Ricotta, Riccardo; Noonan, Douglas M.; Albini, Adriana; et al. (Frontiers in Oncology, 2021)
Reliable liquid biopsy-based tools able to accurately discriminate prostate cancer (PCa) from benign prostatic hyperplasia (BPH), when PSA is within the “grey-zone” (PSA 4-10), are still urgent. We analyzed plasma samples from a cohort of 102 consecutively recruited patients with PSA levels between 4 and 16 ng/ml, using the SANIST-Cloud Ion Mobility Metabolomic Mass Spectrometry platform combined with the analysis of a panel of circulating microRNAs (miR). By coupling CIMS ion mobility technology with SANIST, we were able to reveal three new structures among the most differentially expressed metabolites in PCa vs BPH. In particular, two were classified as polyunsaturated ceramide ester-like and one as polysaturated glycerol ester-like. Penalized logistic regression was applied to build a model to predict PCa using 6 circulating miR, 7 circulating metabolites and demographic/clinical variables as covariates. Four circulating metabolites, miR-5100 and age were selected by the model and the corresponding prediction score gave an AUC of 0.76 (C.I.=0.66-0.85). No high-risk tumor was misclassified and 22 over 53 BPH were correctly identified, reducing by 40% the false positives of PSA. We developed and applied a novel, minimally invasive, liquid biopsy-based powerful tool to characterize novel metabolites and identified new potential non-invasive biomarkers to better predict PCa when PSA is uninformative as tool for precision medicine in genitourinary cancers.